2021
DOI: 10.3390/vaccines9070786
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Protein Vaccine Based on Ag85B and STEAP1 Induces a Protective Immune Response against Prostate Cancer

Abstract: (1) Background: There are currently limited treatments for castration-resistant prostate cancer. Immunotherapy involving Sipuleucel-T has increasingly drawn attention for prostate cancer management. BCG plays a vital role in treating bladder cancer, mainly by inducing immune activation, but is rarely used for prostate cancer. (2) Methods: The TCGA database, PCR, and Western blotting were used to analyze the expression of STEAP1 in mouse and human tissues. Then, we constructed a fusion protein vaccine with Myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Research on the relationship between STEAP1 and tumor characteristics is still in its infancy; however, this relationship has been studied extensively in prostate cancer. As a promising candidate target, STEAP1 has been a recent focus of a number of studies targeting prostate cancer, such as antibody-drug conjugation therapy [15] , T cell immunotherapy [16] , fusion protein vaccines [17] , and the early detection of metastatic prostate cancer [11] . The expression pattern of STEAP1 varies among tumor types, and the role of STEAP1 in different aspects of malignant tumor phenotypes is controversial [5] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Research on the relationship between STEAP1 and tumor characteristics is still in its infancy; however, this relationship has been studied extensively in prostate cancer. As a promising candidate target, STEAP1 has been a recent focus of a number of studies targeting prostate cancer, such as antibody-drug conjugation therapy [15] , T cell immunotherapy [16] , fusion protein vaccines [17] , and the early detection of metastatic prostate cancer [11] . The expression pattern of STEAP1 varies among tumor types, and the role of STEAP1 in different aspects of malignant tumor phenotypes is controversial [5] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Wallis et al subsequently developed liposomal vaccine particles that displayed ErbB-2 and encapsulated OVA 323-339 peptides to improve antibodies against the cancer surface protein ErbB-2, also known as HER-2. 211 Leveraging pre-existing T cells can accelerate GC formation and amplify the magnitude of GC responses, [212][213][214][215] but the expansion on antigen-specific B cells appears to be minimal in other studies. 216 Additionally, while the enhancement effect is clearly T cell epitope dependent, the exact phenotype of the effector T cells involved in this process remains unclear.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Given its localization to surface cell–cell junctions, particularly that of the prostatic secretory epithelium, STEAP1 is a promising target for T-cell and antibody-based immunotherapy [ 61 , 62 ]. Because STEAP1 is overexpressed in malignant prostate tissue but expressed at low levels in normal prostate tissue, STEAP1 is an ideal therapeutic target ( Table 1 ) [ 59 , 60 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Steap1–4 As Biomarkers and Therapeutic Targets For Prostate ...mentioning
confidence: 99%
“…In vitro cytotoxicity assays demonstrated that these epitopes induced strong CTL-mediated antitumor activity [ 80 ]. Other approaches for targeting STEAP in PCa include fusion protein vaccines, RNA–lipoplex vaccines, recombinant viral vaccines, DNA vaccines, and CAR-T cells [ 64 , 65 , 66 , 67 , 73 ]. These studies are promising, and there is much work to do before they can be translated into PCa therapeutics.…”
Section: Steap1–4 As Biomarkers and Therapeutic Targets For Prostate ...mentioning
confidence: 99%